The Level of Implementation of Co-Teaching and its Differences Among Teachers Teaching in Inclusive Classrooms - Ateh, Mohd Arifudin; Tahar, Mohd Mokhtar (Journal of ICSAR, 2020)
The co-teaching approach has been practiced in inclusive classes in several countries globally, but its implementation in developing countries such as Malaysia is still early. Therefore, this study aims to survey the implementation of co-teaching components in inclusive classrooms. This quantitative study adapted the questionnaire from Hussin (2017) administered to 20 mainstream teachers and 20 special education teachers in a district in the state of Selangor, Malaysia. The entire items have a reliability level of 0.908. The data analyzed using descriptive analysis and inference analysis. Vygotsky's Constructivist Theory underlying this study and the model of co-teaching by Friend and Cook were adapted. The findings showed that the implementation level of the co-teaching components was at a moderate level (Mean = 3.90, SD = 0.42), and there was no difference between teacher categories towards the implementation of the co-teaching components with t (38) = -0.387, p= 0.701 (p> 0.05). Those findings indicated that the co-teaching components' implementation level could be further enhanced through the teachers' training and professional development. The initiatives can improve the teacher's understanding of the co-teaching components for more effective implementation. In addition, the combination of field expertise and an equivalent commitment from mainstream and special education teachers will positively impact the teaching and learning process in the inclusive classroom. In conclusion, the tremendous implementation of co-teaching components can improve teaching quality in inclusive education classes and fulfill the special education students’ needs and access to education.